Pressure ulcer prevention in intensive care unit: the care on nurses' optics - Correia, Dayse Mary da Silva; Batista, Deyse Conceição Santoro (Revista de Enfermagem UFPE on line, 2009)
This research deals with prevention of the pressure ulcers in Intensive Care Unit, in the optics of nursing care. Research questions: Which nursing cares are undertaken by ICU nurses for preventing the pressure ulcer? How nurses understand their assistance in the pressure ulcer prevention ? Objectives: to characterize the nursing care fulfilled for nurses in the ICU related to the prevention of pressure ulcer; to discuss what nurses think about their nursing assistance for preventing pressure ulcer and to analyze the approximation and distancing extent in speech by nurses concerning prevention of pressure ulcer. This is a qualitative, descriptive and explorative study joining 08 nurses, and adopting three moments: a sensibility dynamic, with individual production, group discussion and an individual semi-structured interview. Therefore this way, it was possible to realize what and how nurses think about their participation in the prevention and appearance of pressure ulcer context in the ICU; their conflicts facing the multiprofessional responses; and the human aspects – sensible and ethics – implicated on care. Keywords: nursing; nursing care; pressure ulcer.